Low-frequency observations of the giant radio galaxy NGC 6251. Issue 1 (4th May 2020) - Cantwell, T M; Bray, J D; Croston, J H; Scaife, A M M; Mulcahy, D D; Best, P N; Brüggen, M; Brunetti, G; Callingham, J R; Clarke, A O; Hardcastle, M J; Harwood, J J; et al.
ABSTRACT: We present LOFAR observations at 150 MHz of the borderline FRI/FRII giant radio galaxy NGC 6251. This paper presents the most sensitive and highest resolution images of NGC 6251 at these frequencies to date, revealing for the first time a low-surface-brightness extension to the northern lobe, and a possible backflow associated with the southern lobe. The integrated spectra of components of NGC 6251 are consistent with previous measurements at higher frequencies, similar to results from other LOFAR studies of nearby radio galaxies. We find the outer structures of NGC 6251 to be either at equipartition or slightly electron dominated, similar to those of FRII sources rather than FRIs, but this conclusion remains tentative because of uncertainties associated with the geometry and the extrapolation of X-ray measurements to determine the external pressure distribution on the scale of the outer lobes. We place lower limits on the ages of the extension of the northern lobe and the backflow of the southern lobe of t ≳ 250 Myr and t ≳ 210 Myr, respectively. We present the first detection of polarization at 150 MHz in NGC 6251. Taking advantage of the high Faraday resolution of LOFAR, we place an upper limit on the magnetic field in the group of $B \lt 0.2 \, (Λ _B / 10\, {\rm kpc})^{-0.5}\, μ$ G for a coherence scale of $Λ _B \lt 60\, {\rm kpc}$ and $B \lt 13\, μ G~for Λ _B = 240$ kpc.